Genetic alterations in myeloproliferative and myelodysplastic/myeloproliferative neoplasms: a practical guide to WHO-HAEM5 - Kühn, Constanze; Hörst, Katharina; Kvasnicka, Hans M.; Hochhaus, Andreas; Reiter, Andreas (Medizinische Genetik, 2024)
Within the World Health Organization (WHO) classification of haematopoietic neoplasms, particularly its fifth version from 2022 (WHO-HAEM5), myeloid neoplasms are not only grouped into myeloproliferative (MPN) and myelodysplastic neoplasms (MDS). There is also a group of haematological disorders that share features of both categories termed myelodysplastic /myeloproliferative neoplasms (MDS/MPN). In this article, we aim to provide a comprehensive and practical guide to WHO-HAEM5 highlighting the genetic alterations that underlie MPN and MDS/MPN. This guide provides an overview of the overlapping commonalities among these entities, as well as their unique characteristics.